A new awakening: Colombia’s recent foreign policy shift and its impact on the internal conflict - Puerto Castro, Diana Carolina (2011)
Colombia has been historically aligned to the United States who has become one of the main destinations of Colombian exports as well as the leading sponsor in the fight against drugs and the guerrilla groups. This work investigates the causes and possible impacts of the shift in Colombia’s foreign policy on the internal conflict. Furthermore, it is pointed out the way the shift could affect the conflict as well as feasible scenarios for the future.